Compound heterozygous microdeletion of chromosome 15q13.3 region in a child with hypotonia, impaired vision, and global developmental delay. Issue 7 (3rd April 2014) - Prasun, Pankaj; Hankerd, Michael; Kristofice, Melissa; Scussel, Lindsey; Sivaswamy, Lalitha; Ebrahim, Salah
<x xml:space="preserve">Abstract</x> Homozygous or compound heterozygous microdeletion of 15q13.3 region is a rare but clinically recognizable syndrome manifested by profound intellectual disability, muscular hypotonia, intractable seizures, and visual impairment. We identified a compound heterozygous 15q13.3 microdeletion in a 23‐month‐old girl with global developmental delay, generalized muscular hypotonia, and visual dysfunction. The larger deletion was approximately 1.28 Mb in size and contained seven genes including the TRPM1 and CHRNA7, while the smaller deletion was estimated to be 410 Kb in size and contained only CHRNA7. Compound heterozygous 15q13.3 microdeletion is extremely rare and to the best of our knowledge only two such patients have been reported in literature thus far. The findings in our patient suggest that the pathogenesis of visual dysfunction, which is a consistent finding in homozygous/compound heterozygous 15q13.3 microdeletion depends upon the size of microdeletion. Homozygous loss of TRPM1 likely causes retinal dysfunction while homozygous loss of CHRNA7 alone may lead to visual impairment by cortical mechanisms. © 2014 Wiley Periodicals, Inc.